Europe’s Energy Crisis; Winners of the Crisis with Market Data - Erkan , Anıl Çağlar; Gürsoy, Samet; Doğan, Mesut; Alshiqi, Sevdie (Ekonomika, 2023)
Prices of natural gas, coal, and electricity have risen to the highest level of the last ten years in the last quarter of 2021. It’s possible to express that energy prices in 2021 were much higher, compared to the crisis of 2020’s Covid-19 breakout’s historical descent in the first few months. There are a few factors to this rally. The epidemic caused structural fractions on a global scale. But in general, there is no doubt that crisis factors, which mainly concern Europe, are not limited (with) recovery process in the economy. With this notion, the main structure of this work’s subject aims to analyze the lead-up to the energy crisis that became apparent in 2021. Also, in the work, the energy crisis that’s been occurring will be analyzed thoroughly, with the help of its dynamics and causes. Within the scope of the study, the Hatemi-J (2012) asymmetric causality test was run using the weekly stock closing data of EU natural gas prices (EUGP), Gazprom (XGASPR), and Equinor (XEQUNR) for the period 05.11.2017–28.11.2021. As a result of the analysis, a causal relationship between the variables was determined. However, the work will positively contribute to the literature, being a guide to the current situations and overcoming the similar crisis that might occur in the future.
Keywords: Energy Crisis; Energy Prices; Natural Gas; Gazprom; Equinor